Optical, Electrical and Photoresponsive Properties of Cu2NiSnS4 Solar Detectors - Ilhan, Mustafa; Koc, Mumin Mehmet; Coskun, Burhan; Yakuphanoğlu, Fahrettin (Springer, 2020)
Sol-gel methods were used to fabricate Al/p-Si/Cu2NiSnS4/Al quaternary functional solar detectors. Diffraction, spectroscopy and microscopy were used for the structural characterization of the photodetectors. The bandgap energy was found to be 1.20 eV. The photodiodes exhibited high absorption characteristics in the visible region, with low reflectance. The photosensitivity, photoresponse, linear dynamic range, barrier height and ideality factor of the photodiodes were characterized. I-V and I-t characteristics of the detectors revealed that they are responsive to light. Detectors also show rectifying behaviour. The electrical properties of the detectors were assessed using C-V, G-V, C-adj-V and G(adj)-V plots. Electrical properties were found to be a function of AC signal properties. Such properties are attributed to the existence of interface states. The density of interface states (D-it) calculations of the detectors was performed where reduced density of interface state characteristics for increased frequency was seen.
Keywords: Cu2NiSnS4 solar detectors; quaternary functional photodetectors; optoelectrical properties; photodiodes